PLS-SEM MEASUREMENT MODEL VALIDATION OF SOCIAL MEDIA NEEDS, PATIENT EMPOWERMENT, AND QUALITY OF LIFE IN CHRONIC PATIENTS - Loo Tze Yong; Cheah Whye Lian; Helmy Hazmi (Malaysian Journal of Public Health Medicine, 2026)
The increasing burden of chronic diseases highlights the need to improve patients’ quality of life through a holistic approach that considers the potential of social media to fulfil their needs and empower them. This study aimed to develop and validate a measurement model integrating social media needs, patient empowerment, and quality of life, tailored to Malaysian primary care. The proposed model comprised seven constructs: affective needs, cognitive needs, diversion needs, personal integrative needs, social integrative needs, patient empowerment, and quality of life domains, including physical health, psychological health, social relationships, and environmental health. Content validation by experts and face validation ensured the adapted instruments were appropriate and clearly understood. Data was collected through purposive sampling of 130 chronic patients from selected clinics in Sibu. Measurement model assessments were conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS to validate the constructs, including a higher-order reflective–reflective construct assessed with the disjoint two-stage approach. Results showed that all 50 indicators met convergent and discriminant validity criteria. Indicator loadings exceeded recommended thresholds, average variance extracted values were above 0.5, and composite reliability values were satisfactory. Discriminant validity was confirmed using the Fornell–Larcker criterion, cross-loadings, and the HTMT ratio with a bootstrapping procedure of 10,000 samples. These findings provide evidence that the validated model can reliably assess how social media needs and patient empowerment relate to quality of life among chronic patients in Malaysia. This measurement model offers a strong foundation for future research and practical use in primary care.